Savages opposed to progress ?: Historical and anthropological approaches to indigenous mobilizations in the Peruvian Amazon - Espinosa, Óscar (2009)
This article aims to provide some clues for understanding indigenous mobilizations occurred in recent years in the Peruvian Amazon, especially for the tragic events that took place in the vicinity of  the city of Bagua in June 2009. The first part depicts the historical construction of some of the images and prejudices that Peruvian society has had about the Amazonian indigenous people. This section gives special attention to two of these images: that of the «savage» indian (and its most extreme form: the cannibal) as well as the image of the indian as «naive» and «ignorant». The second part briefly reviews the long history of indigenous struggle for the defense of their territories and culture, as well as the changes in the way they organized this struggle during the last decades.A final step is to analyze what is at stake and lies behind the demands and mobilizations of recent years.